Fraud Pentagon Theory, Financial Stability, and Information Asymmetry in Detecting Financial Statement Fraud (An Empirical Study of Insurance Companies Listed on the Indonesia Stock Exchange, 2018–2022) - Irawan, Bambang (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2026)
This study aims to examine the effects of fraud pentagon factors, financial stability, and information asymmetry in detecting financial statement fraud in insurance companies listed on the Indonesia Stock Exchange during the 2018–2022 period. The fraud pentagon factors consist of pressure, opportunity, rationalization, capability, and arrogance, which are proxied by financial target, ineffective monitoring, change in auditor, change of director, and political connection. Financial statement fraud is measured using the F-Score model. This research employs a quantitative approach using secondary data obtained from annual reports of insurance companies. The sample was selected using purposive sampling and consisted of 15 insurance companies, resulting in 75 firm-year observations. Data were analyzed using logistic regression with SPSS version 27. The results show that ineffective monitoring has a significant effect on financial statement fraud. Meanwhile, financial target, change in auditor, change of director, political connection, financial stability, and information asymmetry do not have significant effects on financial statement fraud. These findings indicate that weak monitoring mechanisms may increase the likelihood of financial statement fraud, while other fraud pentagon factors and additional variables do not significantly explain fraud detection in the observed insurance companies.